Վահրամաբերդ–Մարմաշեն–Տիրաշենի պատմությունից - Սերգեյ Հարությունյան (ՀՀ ԳԱԱ հրատ.)
Мармашен, раскопки которого ведутся с 1972 г., был известен как культовый центр. После строительства Мармашенского монастыря центр культурно-просветительной работы перемещается в Мармашен, где Еремия и за ним Состенэс добиваются определенного успеха в борьбе с католическим мировоззрением среди армянского духовенства. Тирашенская–Мармашенская крепости защищали культовые центры от нашествия турок-монголов с восточной и северной стороны, а от Византийской империи – с западной и южной. Marmashen, excavations of which have been conducting since 1972 was known as a cult centre. After the construction of Marmashen monasterial complex the centre of cultural–elucidative work moved to Marmashen, where Yeremiya and later Sostenes succeeded in the struggle with the Roman world outlook among Armenian priesthood. Tirasen–Marmashen fortresses defended the cult centres from encroachments of Turks–Seljuks from east and north, and from the Byzantine Empire from west and south.
Keywords: History; Auxiliary Sciences of History; CC Archaeology; D History; N Fine Arts; NA Architecture